Lipopolysaccharide Downregulates CD163 Expression to Inhibit PRRSV Infection via TLR4-NF-κB Pathway - Zhu, Zhenbang; Zhang, Hui; Zhang, Xiaoxiao; He, Sheng; Dong, Wenjuan; Wang, Xiaoying; Chen, Yaosheng; Liu, Xiaohong; Guo, Chunhe (Frontiers in Microbiology, 2020)
Porcine reproductive and respiratory syndrome virus (PRRSV) has been recognized to induce proinflammatory cytokine production and modulate the host interferon (IFN) system. Proinflammatory cytokines and type I IFNs contribute to the prevention of viral infection. Lipopolysaccharide (LPS), a specific agonist to Toll-like receptor 4 (TLR4), provokes signal transduction and activates immune response in vivo and in vitro. Here we identified LPS inhibited PRRSV infection in porcine alveolar macrophages (PAMs) and in Marc-145 cells. To investigate the possible mechanism, we found TLR4-NF-κB pathway was obviously activated in LPS-treated PAMs at the early stage of PRRSV infection. As a result, the expression of proinflammatory cytokines was strongly induced following LPS and PRRSV co-treatment. Due to the enhanced proinflammatory response, CD163 expression was significantly reduced and a disintegrin and metalloproteinase 17 was activated, which promotes the cleavage of membrane CD163. Ultimately, CD163 down-regulation led to the suppression of PRRSV replication. Our data demonstrate that LPS has an impact on PRRSV infection via inflammation response, which provides a new insight of inflammation-mediated antiviral immunity and a new strategy to control PRRSV infection.